Changes of perceived stress among undergraduate pharmacy students in International Islamic University Malaysia: Two years longitudinal study - Soe, May Khin Soe; Abdul Rahman, Mohammad Nasrin; Mohd Noor Zaidi, Muhammad Ridzuan; Shamsudin, Siti Hadijah; Zaini, Syahrir (2016)
This study compares the students’ perceived stress scale (PSS score) and their physiological status after two (2) years period of studying the Pharmacy programme. The data of the study done in 2014 were compared with the previous study which was conducted in 2012. This study focused on changes of same students’ PSS score when they were in the first year and third year since there were changes in academic burdens and study environment for them. Moreover, study was aimed to compare the changes of the PSS score between two different genders, identifying the correlation between the PSS score and their physiological status, such as body mass index (BMI), waist circumference, fat percentage and their blood pressure. PSS score was measured by using a set of questionnaire to determine the severity of their stress and find out their solutions to overcome the condition. As a result, mean PSS value in male and female in third year was higher than that of in first year. Males’ PSS score (30.13± 6.62) in the year 3 was significantly higher than their score (24.26 ± 6.53) taken in the year 1. PSS score (30.8±4.89) of the whole class in year 3 was also significantly higher than year 1 scoring (26.14±5.94). Moreover, students’ BMI and fat percentage were found higher in year 3 compare to year 1 but the changes were insignificant. There is significantly higher in students’ systolic blood pressure in 2014 compared to 2012. This study highlighted that academic stress among Pharmacy students is increasing within a 2 year period.